Comparative Ionomics and Metabolic Responses and Adaptive Strategies of Cotton to Salt and Alkali Stress - Guo, Jiaxin; Lu, Xiaoyu; Tao, Yifan; Guo, Huijuan; Min, Wei (Frontiers in Plant Science, 2022)
Soil salinization and alkalization severely inhibit agriculture. However, the response mechanisms of cotton to salt or alkali stress are unclear. Ionomics and metabolomics were used to investigate salt and alkali stresses in cotton roots and leaves. Compared with the control, salt-treated and alkali-treated cotton plants showed 51.8% and 53.0% decreases in biomass, respectively. Salt stress inhibited Ca, B, N, and Fe uptake and Mg, K, P, S, and Cu transport, but promoted Mo, Mn, Zn, Mg, K, P, S, and Cu uptake and Mo, Mn, Zn, B, N, and Fe transport. Alkali stress inhibited P, Ca, S, N, Fe, and Zn uptake and Mg and B transport, but promoted K, Mn, Cu, Mo, Mg, and B uptake and K, Mn, Cu, Mo, Fe, and Zn transport. Under salt stress in the leaves, 93 metabolites, mainly organic acids, amino acids, and sugars, increased in abundance, while 6 decreased. Under saline stress, 72 and 18 metabolites increased and decreased, respectively, in the roots, mainly amino acids and organic acids. Under alkali stress, 96 and 83 metabolites increased and decreased, respectively, in the leaves, including organic acids, amino acids, and sugars. Under alkali stress, 108 and 73 metabolites increased and decreased, respectively, in the roots, including organic acids, amino acids, and sugars. Under salt stress, significant metabolic pathways in the leaves and roots were associated with amino acid and organic acid metabolism, while under alkali stress, the pathways in the leaves were related to amino acid and linoleic acid metabolism. Under alkali stress, the pathways were related to organic acids, amino acids, and sugars. Under salt stress, organic acids, amino acids, and sugars accumulated, while under alkali stress, osmoregulation was achieved via inorganic ion accumulation. Enhancing organic acid accumulation and metabolism in the roots is the key response mechanism of cotton to alkalinity.